Comparative physiological, metabolomic, and transcriptomic analyses reveal mechanisms of apple dwarfing rootstock root morphogenesis under nitrogen and/or phosphorus deficient conditions - Xie, Bin; Chen, Yanhui; Zhang, Yanzhen; An, Xiuhong; Li, Xin; Yang, An; Kang, Guodong; Zhou, Jiangtao; Cheng, Cungang (Frontiers in Plant Science, 2023)
Nitrogen (N) and phosphorus (P) are essential phytomacronutrients, and deficiencies in these two elements limit growth and yield in apple (Malus domestica Borkh.). The rootstock plays a key role in the nutrient uptake and environmental adaptation of apple. The objective of this study was to investigate the effects of N and/or P deficiency on hydroponically-grown dwarfing rootstock ‘M9-T337’ seedlings, particularly the roots, by performing an integrated physiological, transcriptomics-, and metabolomics-based analyses. Compared to N and P sufficiency, N and/or P deficiency inhibited aboveground growth, increased the partitioning of total N and total P in roots, enhanced the total number of tips, length, volume, and surface area of roots, and improved the root-to-shoot ratio. P and/or N deficiency inhibited NO3- influx into roots, and H+ pumps played a positive role in the response to P and/or N deficiency. Conjoint analysis of differentially expressed genes and differentially accumulated metabolites in roots revealed that N and/or P deficiency altered the biosynthesis of cell wall components such as cellulose, hemicellulose, lignin, and pectin. The expression of MdEXPA4 and MdEXLB1, two cell wall expansin genes, were shown to be induced by N and/or P deficiency. Overexpression of MdEXPA4 enhanced root development and improved tolerance to N and/or P deficiency in transgenic Arabidopsis thaliana plants. In addition, overexpression of MdEXLB1 in transgenic Solanum lycopersicum seedlings increased the root surface area and promoted acquisition of N and P, thereby facilitating plant growth and adaptation to N and/or P deficiency. Collectively, these results provided a reference for improving root architecture in dwarfing rootstock and furthering our understanding of integration between N and P signaling pathways.